FSKTM Faculty Room Reservation System - MOHD NAJIB, MUHAMMAD SHAHRUL ILHAN; MOHD NAWI, NAZRI (Applied Information Technology And Computer Science, 2026)
The room booking process at the Faculty of Computer Science and Information Technology (FSKTM), UTHM, still relies on manual methods, often leading to confusion, overlapping reservations, and delayed confirmations. The absence of an efficient system makes it difficult for administrators to manage room reservations, especially as the number of users increases. Therefore, this project develops a web-based information system, known as BookIT, to modernize and centralize the room booking process at the faculty. The primary objective of this project is to create an automated booking system that allows users, such as students, lecturers, and administrative staff, to make reservations more efficiently and systematically. This project adopts the Agile methodology, which involves phases of requirements gathering, development, testing, and maintenance in iterative cycles. The system is designed using web technologies such as HTML, CSS, and JavaScript for the user interface, while PHP and MySQL are used for backend development and database management. Key features include real-time availability, automated booking, schedule conflict management, as well as automated notifications and booking confirmations. The system is also equipped with security features such as user authentication and data encryption to ensure information integrity. BookIT can improve booking efficiency, reduce manual errors, and accelerate the reservation approval process. Furthermore, the system also able to reduce administrative workload and enhance user experience.